(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This article considers the methodology of hydraulic calculation of ring gas distribution systems on the example of a network with one supply and one withdrawal node. In the course of the analysis the advantages of the ring structure over the beam structure are revealed, the regularities of pressure and gas flow distribution are substantiated, and the methods of calculation of looped sections of main gas pipelines are considered. Particular attention is paid to the situation where the ring network includes a single feeder node and a limited number of withdrawal nodes. The analysis concludes with a discussion of a computational experiment.